Effects of 21 days of intensified training on markers of overtraining - Slivka, D. R.; Hailes, W. S.; Cuddy, J. S.; Ruby, B. C. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to impose a period of quantifiable intensified training to determine if commonly used diagnostic markers of overtraining parallel changes in physical performance and thus overtraining status. Eight trained male cyclists (24 ± 1 years, 71 ± 3 kg, VO2peak = 4.5 ± 0.1·L/min) performed 21 days (3,211 km) of intensified training in the field where volume and intensity were increased over normal training. Salivary IgA, testosterone, and cortisol, 1-hour time trial performance, heart rate response, and profile of mood states (POMS) were collected and analyzed throughout the 21-day training period. The POMS category vigor declined from day 1 to day 4 and remained lower throughout (p < 0.05). There were no other statistical changes in overtraining parameters. However, individuals who demonstrated 2 or more symptoms of overtraining at any point throughout the 21 days were considered symptomatic and had a lower (p < 0.05) VO2peak (4.2 ± 0.1·vs. 4.7 ± 0.1 L/min) and lower (p < 0.05) average workload during the initial 1-hour time trial (253 ± 5 vs. 288 ± 14 W). Interestingly, the 1-hour time trial power in these individuals with symptoms of overtraining did not decline (p > 0.05). These data demonstrate that markers of overtraining do not parallel a decrease in performance and should be interpreted with caution.